Relapse of Pulmonary Tuberculosis in Patients with Resistance to Isoniazid - I. A. Burmistrova; O. V. Lovacheva; A. G. Samoylova; I. A. Vasilyeva (Туберкулез и болезни лёгких)
The objective: to study the incidence of relapses over a two-year period after successful completion of chemotherapy in patients with isoniazid-resistant tuberculosis (Hr TB), to determine the risk factors for relapses in this cohort.Subjects and Methods. The medical records of 1860 Hr-TB patients who started treatment in 2015 in TB hospitals in 18 regions of the Russian Federation were retrospectively studied. Of these, 1271 (68.3 ± 1.08%) patients successfully completed a full course of chemotherapy, which were divided into two groups depending on the presence/absence of relapse in the next two years.Results. Tuberculosis relapse was observed in 131/1271 (10.31%; CI 8,75–12,10%) (R+ Group) patients, the remaining 1140 patients(R– Group) developed no relapse. For R+ and R– Groups, the first episode of the disease (FED) was analyzed, for R+ Group, the episode of the disease recurrence detection (DRD) was also analyzed. The risk factors for relapse development include the following parameters that were available in patients during first episode of the disease: unemployment at working age (OR=1,98; 95% CI [1,36–2,88]), diabetes mellitus or chronic alcohol addiction (OR=3,93; 95% CI [2,13–7,26%] and OR=2,25; 95% CI [1,02–5,01]), lung tissue decay OR=2,01; 95% CI [1,31–3,07], and drug resistance of Mycobacterium tuberculosis (H+Ag+Fq) (OR=7,26; 95% CI [3,90–10,62]).With the disease recurrence detection, out of 131 patients of R+ Group, the positive results of the sputum test was recorded only in 117 (89,3%) patients, 41/131 (31,3%) patients developed a different clinical form of tuberculosis versus the first episode of the disease, and in 12/41 ( 29,3%) or 12/131 (9,2%) patients, the disease was more severe. 44/117 (37,6%) patients had been already resistant to rifampicin. It means they had developed MDR TB before the relapse was detected.